L’étalement résidentiel des métropoles intermédiaires de la région Centre Val de Loire - Jean-Marc Zaninetti (OpenEdition, 2018)
The Loire Valley cities of Tours and Orleans are good examples of France’s urban housing sprawl after WW2. Since the turn of the century, French authorities have tightened urban development regulations to support residential densification. Cities like Tours and Orléans barely showed a change in development before 2013. Using MAJIC’s real estate data, a comparison of the two metropolitan areas displays more resemblance than differences despite very different political arrangements and different metropolitan governance. The timeline of housing development reflects nationwide housing policies. While central cities — notably Tours — actively promote housing densification, other communities still rely on scattered greenfield development of single family homes in the outlying “urban countryside”, resulting in a spotted, “leopard-skin” pattern of sprawling villages. With abundant and affordable land and reduced construction costs, the development of individual homes has a competitive edge that is hard to overcome for promoters of urban “renewal” trying to sell apartments in new, densely populated urban neighbourhoods.